Differences In The Effectiveness Of Date Juice And Beet Juice In Increasing Hemoglobin Levels In Anemia Pregnant Women In The Work Area Of The Tirtamulya Health Center In 2023 - Lia Sakti Herlianti; Melisa Putri Ramadhena (CV. Inara, 2024)
Background: beets and dates can increase hemoglobin for those who have anemia. The nutritional composition of dates is that they are rich in natural sugars, fiber, potassium, magnesium and B vitamins, iron, calcium and phosphorus in fairly high amounts, while beets also contain nitrates, compounds that can help improve blood flow and performance. brain so that it can be known to increase hemoglobin levels in the blood. Purpose of writing: to find out the difference in the effectiveness of giving date juice and beet juice in increasing hemoglobin levels in anemic pregnant women in the working area of the Tirtamulya Health Center in 2023. Research method: Pre-experimental study with type one group pre test – post test design by means of relationships cause and effect by involving a group of subjects. the subject group was observed before the intervention was carried out and then observed after the intervention was carried out. The sampling technique is non-probability sampling with a purposive method. The study was divided into 2 variables, namely the independent variable, namely the consumption of date juice and beetroot juice. Results: Assessment before and after administration of date palm juice obtained a value of Sig 0.000, sig value <0.05 which can be concluded that there is effectiveness of giving date juice in increasing Hb levels in anemic pregnant women. While theassessment before and after giving beetroot juice obtained a Sig value of 0.000, a sig value <0.05 which can be concluded that there is effectiveness of giving beetroot juice in increasing Hb levels in anemic pregnant women. Conclusions and Suggestions: The results of this study are expected to provide information that giving date palm juice and beetroot juice is a type of natural food that can increase Hb levels.